Adsorption of phenol from aqueous solutions using incinerated sewage sludge - Wan Mohamed, Wan Afnizan (2004)
A study had been carried out to detennine the potential use of sewage sludge ash (SSA) as an adsorbent in removing phenol from aqueous solution. Parameters which contributed to affect phenol removal were initial phenol concentration, contact time, adsorbent dosage, pH and particle size of adsorbent. Results showed that the adsorption capacities of adsorbent (Kf) for phenol decreased from 14.89 mg/g to 0.68 mg/g as initial phenol concentration increased from 0.1 mg/l to 5.0 mg/l. Results revealed that solution with higher initial phenol concentration required longer time to reach equilibrium state. Adsorption capacity of adsorbent (Kf) decreased from 14.89 mg/g to 0.66 mg/g as contact time increased from 240 minutes to 1200 minutes. Furthermore, pH was found to affect the adsorption capacity where as pH decreased from original (9 - 12) to neutral (7 - 8), adsorption capacity of adsorbent increased from 0.68 mg/g to 3.0 mg/g. Moreover, it was shown that as particle size of adsorbent decreased from 150 - 212 ~ to 63 - 149 ~, adsorption capacity of adsorbent (Kf) was decreased from 2.06 mg/g to 0.68 mg/g. Adsorption isotherm analysis showed that the experimental data fit Freundlich model in most conditions.